Perception of Nursing students and their Preceptors on concept mapping as a clinical learning tool - Jasmine Joseph, Archana Pradhan, Anamika Pradhan, Jijo J, Shanesh Rai, Tika Devi Chettri, Ranjitha G (International Journal of Advanced Science and Technology, 2020)
Clinical learning is an indispensable component of the nursing training curriculum. However, there is little nursing educational research available regarding the effective delivery of theoretical knowledge into clinical training. By utilizing the concepts of concept mapping and applying it in care of hospitalized patients, clinical learning skills of a nursing student can be strengthened (van Graan, Williams & Koen, 2016). Identifying the perception of the students and their preceptors will help in the successful implementation of concept mapping as an effective clinical learning instrument. The purpose of the study was to implement concept mapping in clinical leaning and assess the perception of nursing students and their preceptors on concept mapping as a clinical learning tool. The study was conducted at two nursing colleges in Bangalore. Convenient sampling technique was used to identify the two nursing colleges and Baccalaureate nursing II and III-year students studying in this college was included for the study (N=136). Total enumeration sampling technique was used for the study and 136 Nursing students and 30 preceptors were enrolled for the study. The perception of the students and preceptors were collected by using a self-administered Likert scale followed by a group discussion. Students and their preceptors found concept mapping as a useful tool for clinical learning. Majority of the students 85 (62.5 %) and the preceptors 22 (70.97%) had a very positive opinion regarding concept mapping. None of the preceptors and three (2.2%) of students had a negative perception regarding concept mapping. Concept mapping was viewed as a useful approach to clinical learning by providing learners to link additional knowledge and clinical skills to previous learning. The positive response given by all the students and their preceptor to the concept mapping activity in the clinical setting will support further studies to evaluate its activity to link theory to practice.